2021
DOI: 10.1371/journal.pone.0247509
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes and prognostic factors of vitrectomy for lamellar macular holes and epiretinal membrane foveoschisis

Abstract: Purpose To evaluate the visual outcomes of vitrectomy for lamellar macular hole (LMH) and epiretinal membrane (ERM) foveoschisis and to investigate the prognostic factor for postoperative visual acuity. Methods We retrospectively reviewed 15 LMH and 17 ERM foveoschisis eyes that had undergone a standard three-port pars plana vitrectomy with (12 eyes) or without (20 eyes) cataract surgery. Best-corrected visual acuity (BCVA) at postoperative three months and the final visit were compared to the preoperative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…In conjunction with a relative stabilized natural course, a surgical management is mainly indicated for those patients who experience progressive visual and/or anatomical deterioration. Several authors investigated beneficial effects of vitrectomy for conditions presenting with ERM and intraretinal schisis-like separation (defined as tractional LMH or MPH with stretched/cleavage edge) in terms of post-operative BCVA and OCT foveal structures [ 15 , 21 23 ]. Among those, Gaudric et al reported an overall visual improvement, assessed at 3 months or more post-operation, in both MPH with straight and cleavage foveal edge that had initial VA worse than 20/40 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conjunction with a relative stabilized natural course, a surgical management is mainly indicated for those patients who experience progressive visual and/or anatomical deterioration. Several authors investigated beneficial effects of vitrectomy for conditions presenting with ERM and intraretinal schisis-like separation (defined as tractional LMH or MPH with stretched/cleavage edge) in terms of post-operative BCVA and OCT foveal structures [ 15 , 21 23 ]. Among those, Gaudric et al reported an overall visual improvement, assessed at 3 months or more post-operation, in both MPH with straight and cleavage foveal edge that had initial VA worse than 20/40 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study by Omoto et al, with an application of a consensus OCT definition, has demonstrated a significant visual gain at 3 months and at the final visit for ERM foveoschisis patients who underwent vitrectomy. For the LMH group, a significant visual improvement was observed only at the final visit [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that there was no surgical benefit for eyes with ERP [62]. In contrast, other investigators report that ERP did not affect surgical outcomes [27,49,53,55,131].…”
Section: Treatmentmentioning
confidence: 99%
“…Several pre-operative biomarkers, including pre-operative visual acuity, foveal thickness, ellipsoid zone integrity and the presence of ERP, have been explored as post-operative prognostic factors [ 62 , 130 , 131 ]. A poor pre-operative visual acuity (≤20/100), a thin fovea (≤100 µm), pre-operative ellipsoid zone disruption, absence of vitreopapillary adhesion or the presence of ERP were identified as poor prognostic signs for LMH undergoing surgical repair [ 62 , 130 , 132 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Recommendations for surgical intervention are rather reserved in literature. While studies suggest functional improvement in eyes with ERMF following surgery, most studies found no beneficial effect on VA in LMH (Androudi et al 2009;Casparis & Bovey 2011;Coassin et al 2018;Caretti et al 2020;Omoto et al 2021). Ko et al compared the surgical outcome of LMH with and without EP and found that eyes with EP preoperatively had a greater diameter, thinner fovea and a higher incidence of outer retinal disruption.…”
Section: Discussionmentioning
confidence: 99%